2020
DOI: 10.1007/978-3-030-27492-4
|View full text |Cite
|
Sign up to set email alerts
|

Extemporaneous Ophthalmic Preparations

Abstract: the material is concerned, specifically the rights of translation, reprinting, reuse of illustrations, recitation, broadcasting, reproduction on microfilms or in any other physical way, and transmission or information storage and retrieval, electronic adaptation, computer software, or by similar or dissimilar methodology now known or hereafter developed. The use of general descriptive names, registered names, trademarks, service marks, etc. in this publication does not imply, even in the absence of a specific … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Several factors influence the ocular absorption of topical drugs, which can lead to a delay in penetration in some patients. 21 This may explain the variable intraocular concentrations achieved in our study. According to previous studies, 15 to 20% of cases have shown a poor response to 0.01% atropine.…”
Section: Discussionmentioning
confidence: 69%
“…Several factors influence the ocular absorption of topical drugs, which can lead to a delay in penetration in some patients. 21 This may explain the variable intraocular concentrations achieved in our study. According to previous studies, 15 to 20% of cases have shown a poor response to 0.01% atropine.…”
Section: Discussionmentioning
confidence: 69%